PENGEMBANGAN SISTEM INFORMASI PORTOFOLIO PEMBELAJARAN UNTUK MENDUKUNG MANAJEMAN CAPAIAN PEMBELAJARAN MATAKULIAH BERBASIS OBE (STUDI KASUS DI PROGRAM STUDI TEKNIK INFORMATIKA) - Sri Endang Anjarwani; Moh Ali Albar; Fitri Bimantoro; Nadiyasari Agitha; Ahmad Zafrullah M.; Muh. Gerald Dennaya HD (JTIKA (Jurnal Teknik Informatika, Komputer dan Aplikasinya), 2026)
The Information Technology Study Program (PSTI) implements an OBE-based curriculum to measure graduate achievement (CPL) and course learning achievement (CPMK), requiring lecturers to compile learning achievement reports in the form of portfolios at the end of each semester. The compilation of portfolios is supplemented with CPL and CPMK results calculated using Microsoft Excel. During the preparation of the report, difficulties arise when changing data that affects the formula. Not all lecturers understand the available formulas and equations. The purpose of this research is to develop an information system to support the preparation of lecturers' course learning portfolio reports. The method used is Extreme Programming, which is an Agile software development approach with the stages of Planning, Design, Coding, Testing, and Release Phase (Deploy). This research resulted in a Learning Portfolio Information System to Support OBE-Based Course Learning Achievement Management (Case Study in the Informatics Engineering Study Program). In this information system, lecturers can manage CPL, CPMK, Sub_CPMK, Assessment, Evaluation, Results, and Portfolio data. From testing using User Acceptance Testing, the results obtained were an average of 37% strongly agree, 43% agree, and 19% somewhat agree. Therefore, it can be said that the information system created can be used properly.